Hepatitis C virus related cirrhosis: time to occurrence of hepatocellular carcinoma and death. Issue 1 (1st July 2000) - Degos, F; Christidis, C; Ganne-Carrie, N; Farmachidi, J-P; Degott, C; Guettier, C; Trinchet, J-C; Beaugrand, M; Chevret, S
Abstract : BACKGROUND: In patients with hepatitis C virus (HCV) infection and cirrhosis, long term outcome and the incidence of hepatocellular carcinoma (HCC) are still debated. DESIGN: From January 1987 to January 1997, 416 patients (240 male, median age 57 years) with uncomplicated Child-Pugh A HCV related cirrhosis were followed in two Paris area centres from diagnosis of cirrhosis until death or reference date (1 June 1998). The analysis used a three state disability model generalising the Cox model. RESULTS: Of the 416 patients, 60 developed HCC with a five year rate of 13.4% (95% confidence interval (CI) 9.0–17.8%) and 83 died (including 34 with HCC), with a five year death rate of 15.3% (95% CI 12.6–18.0%). By multivariable analysis, time to HCC relied on age (hazard ratio (HR) 1.05 per year; p=0.0005), male sex (HR 2.13; p=0.01), oesophageal varices (HR 2.36; p= 0.008), decreased platelet count (HR 0.99; p=0.03), and bilirubin level (HR 1.01; p=0.003), while death after HCC was mainly related to tobacco consumption (HR 1.04; p=0.0006). In contrast, death free of HCC was dependent on age (HR 1.04; p=0.01), oesophageal varices (HR 2.75; p=0.001), low platelet count (HR 0.99; p=0.006), and albumin level (HR 0.90; p=0.0001). CONCLUSION: The incidence of HCC and mortality should be higher in these patients than previously stated, and prognostic factors of HCC and death are closely related age and symptoms of portal hypertension.